Determinants of Low Birth Weight at Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia - Erlangga Yusa Bachtiar; Revi Gama Hata Novika; Bhisma Murti; Eti Poncorini Pamungkasari; Setyo Sri Rahardjo (Journal of Maternal and Child Health, 2025)
Background: Low birth weight (LBW) is a major cause of infant and neonatal mortality in Indonesia. Data from the 2022 Nutritional Status Survey and the 2023 Indonesia Health Survey reported an increase in the prevalence of LBW from 5.9% to 6.1%. Records from Dr. Moewardi General Hospital, Indonesia, also show a rise in the number of LBW cases, from 392 cases in 2023 to 412 cases in 2024. This study examines the effects of maternal education, household income, antenatal care (ANC), anemia during pregnancy, preeclampsia, and chronic energy deficiency (CED) on the incidence of LBW at Dr. Moewardi hospital. Subjects and Method: This quantitative study employed a case–control design. The research was conducted at Dr. Moewardi hospital and included 100 infants with low birth weight and 100 infants with normal birth weight, selected using fixed-disease and random sampling methods. The dependent variable was LBW. The independent variables were maternal education, household income, ANC, anemia during pregnancy, preeclampsia, and CED. Data were collected through questionnaires and medical records, and analyzed using simple logistic regression and path analysis.Results: LBW was directly associated with maternal CED (b= 0.79; 95% CI= 0.08 to 1.51; p= 0.028), maternal anemia (b= 0.91; 95% CI= 0.17 to 1.65; p= 0.015), and preeclampsia (b= 1.45; 95% CI= 0.77 to 2.13; p < 0.001). LBW was indirectly influenced by ANC visits, family income, and maternal education. The path model demonstrated good fit indices (AIC= 1221.24; BIC= 1283.91).Conclusion: LBW directly increases with maternal CED, maternal anemia, and preeclampsia. LBW indirectly affects by ANC visit, family income, and maternal education.